Keputusan Pelaku UMKM Dalam Memilih Pembiayaan Berbasis Syariah - Rahman, Taufiqur; Salistia, Faisal; Arsyad, Muhammad Rizal; Romli, Moh. (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
One of the economic goals is economic development. This can be done through strategy MSME. Empowerment MSME is a strategic step improving and strengthening of the economy. With the existence of MSMEs, the government strive to support MSMEs financing programs. In this study the financing program institution studied was Syariah's financial institution of BMT UGT Nusantara, Pegadaian Syariah, and KSPPS Nuri Jatim Socah Bangkalan. The type of research used in this research is qualitative research with descriptive approach. The method used by researchers in collecting the required data is: observation (observation), interview (interview), and documentation. This research uses triangulation method. Researchers recheck findings of various sources. So the drug is the result obtained from observation, interview, and documentation. In this study the result obtained is the factor that undertakes the UMKM customers in choosing the financing product in the Sharia Financial Institution is a cultural factor, social, personal, psychological and from these three financial institutions to compare the reason for customers choosing financing in the financial institution is the product, service, trust and price. This above all affects the UMKM customers in decision-making choosing financing in three syariah financial institutions.